MAKNA SIMBOLIK MANGAN INDAHAN SIPAET-PAET (MAKAN NASI PAHIT) DALAM ACARA MANGAPULI (PENGHIBURAN) ADAT BATAK TOBA SEBAGAI BENTUK KEARIFAN LOKAL DI PEKANBARU - Alexander "; W. E. Tinambunan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The culture is a heritage activity that has own characters which transform asocial life in implementation. The Culture is one of a communication way to eachother which use signs and symbols that have some meanings, and also ManganIndahan Sipaet-paet’s tradition (eat bitter rice) in Mangapuli event (solace) ofToba Bataknese, have the symbols which must be protected and covered becauseit simbolizing hope for new life. This phenomena make a researcher interests inthis research. It goals to know the process of handing out means in “ManganIndahan Sipaet-paet”, symbolic meaning of “Mangan Indahan Sipaet-paet”, andthe values on it.This research uses a descriptive qualitative method, with the informan byaccidental sampling technique. Informan was choosen by incidentally moment.The informan in this research are cultural personal figure and family who had in asorrow moment. The accumulation data technique uses an observation, interview,and documentation.The result of this research means from “Mangan Indahan Sipaet-paet”(eat bitter rice) is a love to regret of sorrow. A love to God and a love to eachother, we care each other, feel the sorrow, and also give some solace for thefamily by praying together.Keywords : Mangan Indahan Sipaet-paet, symbol, tradition